What Developers Want and Need from Program Analysis: An Empirical Study - Christakis, Maria; Bird, Christian (31st International Conference on Automated Software Engineering (ASE'16), 2016)
Program Analysis has been a rich and fruitful field of research for many decades, and countless high quality program analysis tools have been produced by academia. Though there are some well-known examples of tools that have found their way into routine use by practitioners, a common challenge faced by researchers is knowing how to achieve broad and lasting adoption of their tools. In an effort to understand what makes a program analyzer most attractive to developers, we mounted a multi-method investigation at Microsoft. Through interviews and surveys of developers as well as analysis of defect data, we provide insight and answers to four high level research questions that can help researchers design program analyzers meeting the needs of software developers. First, we explore what barriers hinder the adoption of program analyzers, like poorly expressed warning messages. Second, we shed light on what functionality developers want from analyzers, including the types of code issues that developers care about. Next, we answer what non-functional characteristics an analyzer should have to be widely used, how the analyzer should fit into the development process, and how its results should be reported. Finally, we investigate defects in one of Microsoft's flagship software services, to understand what types of code issues are most important to minimize, potentially through program analysis.